Adaptive management in wildlife conservation - Organ, John; Decker, D.J.; McDonald, J.E.; Riley, Shawn; Mahoney, S.P. (The Wildlife Society Techniques Manual, 2012)
Adaptive management in wildlife conservation emerged from the wildlife profession's search for better solutions to increasingly complex cons ervation challenges. Adaptive management is an effective process for w ildlife managers to employ to (1) deal with uncertainty in the managem ent system, (2) learn from their management actions, and (3) achieve d esired results. Being adaptable or flexible in your management approac h is not the same as managing adaptively or conducting adaptive manage ment. Adaptive management requires adhering to a stepwise process and fully executing each step. A critical step is rigorous monitoring and assessment of management interventions. Without this, wildlife manager s cannot achieve the essence of adaptive management, which is the expl icit goal of learning more about the management system after each mana gement action.